Identifying Genetic Etiology in Patients with Intellectual Disability: An Experience in Public Health Services in Northeastern Brazil - de Carvalho, Acacia Fernandes Lacerda; Alves, Esmeralda Santos; Pitanga, Paula Monique Leite; Ribeiro, Erlane Marques; Doriqui, Maria Juliana Rodovalho; Toralles, Maria Betânia Pereira; Topázio, Bianca Arcaro; dos Santos, Jéssica Fernandes; de Lima, Renata Lúcia Leite Ferreira; Kulikowski, Leslie Domenici; Acosta, Angelina Xavier (Journal of Pediatric Genetics, 2022)
Intellectual disability (ID) is considered a common neuropsychiatric disorder that affects up to 3% of the population. The etiologic origin of ID may be genetic, environmental, and multifactorial. Chromosomopathies are relatively common among the genetic causes of ID, especially in the most severe cases and those associated with dysmorphic features. Currently, the application of new molecular cytogenetics technologies has increasingly allowed the identification of microdeletions, microduplications, and unbalanced translocations as causes of ID. The objective of this study was to investigate the etiology of ID in patients admitted to a public hospital in Northeastern Brazil. In total, 119 patients with ID who had normal karyotypes and fragile X exams participated in this study. The patients were initially physically examined for microdeletion syndromes and then tested using fluorescence in situ hybridization (FISH), multiplex ligation-dependent probe amplification (MLPA), methylation-sensitive polymerase chain reaction (MS-PCR), and chromosome microarray analysis (CMA), according to clinical suspicion. Patients with no diagnoses after FISH, MLPA, and/or MS-PCR evaluations were subsequently tested by CMA. The rate of etiologic diagnoses of ID in the current study was 28%. FISH diagnosed 25 out of 79 tested (31%), MLPA diagnosed 26 out of 79 tested (32%), MS-PCR diagnosed 7 out of 20 tested (35%), and the single nucleotide polymorphism array diagnosed 6 out of 27 tested (22%). Although the CMA is the most complete and recommended tool for the diagnosis of microdeletions, microduplications, and unbalance translocations in patients with ID, FISH, MLPA, and MS-PCR testing can be used as the first tests for specific syndromes, as long as the patients are first physically screened clinically, especially in the public health networks system in Brazil, where resources are scarce.
Keywords: intellectual disability; dysmorphism; copy number variation; chromosome microarray analysis; FISH